The Nations’ poverty: An economic dependency’s philosophical análisis - Teruel, Flavio (2025)
This article examines poverty and economic dependency in Latin America from the perspective of Enrique Dussel’s philosophy of liberation. Through a brief genealogy, it analyzes the meanings of dependency in Latin American social thought and its reinterpretation within the Dusselian framework, which connects this theory to a critique of capitalism since 1492. A conceptual framework is proposed that integrates Marx’s critique with the paradigm of liberation, facilitating an analysis of the dynamics of global exploitation from a critical and liberating perspective. The main contribution of the article lies in identifying the correspondence between the categories of the philosophy of liberation and those derived from Marx’s critique of political economy, which allows for an understanding of the mechanisms of exploitation, appropriation, and value transfer in the center-periphery relationship. Finally, the relevance of dependency is evaluated as a philosophical and economic problem, highlighting some contemporary mechanisms of value transfer.